The representation of a political event in cinema: the singing revoliution - Stonytė, Renata (Information & Media, 2015)
The analysis presented in this article reveals the visual representation of non-violent revolutions of 1989 in the Baltic States in documentary films. The film is accepted as having an influence on people’s understanding of historical events and the formation of collective memory. Documentary films How We Played the Revolution (2011) and The Singing Revolution (2006) create a visual representation of a political event and become a source of collective memory. This liberation movement, a fight against communist regime, is represented as a historical epic where society becomes the main character of the film, and emotion-based images strengthen the identity of the group and collective pride.
Keywords: collective memory; documentary film; historical event; visualization